The Fragile World Hypothesis: Complexity, Fragility, and Systemic Existential Risk. (September 2020) - Manheim, David
Highlights: Complex systems are often fragile, and interrelationships make collapses and cascading failures, increasingly dangerous. There is a possible class of existential risk from systemic fragility, related to Bostrom's Vulnerable World Hypothesis. A new "inevitable technological fragility" hypothesis is proposed, specifying how collapse could be unavoidable. The hypothesis is a speculation, rather than an expectation, and the conditions under which it is true are explored. Abstract: The possibility of social and technological collapse has been the focus of science fiction tropes for decades, but more recent focus has been on specific sources of existential and global catastrophic risk. Because these scenarios are simple to understand and envision, they receive more attention than risks due to complex interplay of failures, or risks that cannot be clearly specified. In this paper, we discuss the possibility that complexity of a certain type leads to fragility which can function as a source of catastrophic or even existential risk. The paper first reviews a hypothesis by Bostrom about inevitable technological risks, named the vulnerable world hypothesis. This paper next hypothesizes that fragility may not only be a possible risk, but could be inevitable, and would therefore be a subclass or example of Bostrom's vulnerable worlds. After introducing the titular fragile world hypothesis, the paper details the conditions under which it would be correct, and presents arguments for why the conditions may in fact may apply. Finally, the assumptions and potential mitigations of the new hypothesis are contrasted with those Bostrom suggests.